Clinical and Translational Imaging Reviews in Nuclear Medicine and Molecular Imaging - Lucignani, Giovanni; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
Clinical and Translational Imaging is a peer-reviewed journal specifically devoted to review articles on translational and clinical imaging in the field of nuclear medicine and molecular imaging. The journal is the official journal of the Italian Association of Nuclear Medicine. Authors and Editor from Italy, from Europe and from all parts of the world are contributing. The journal publishes timely and updated summaries on clinical practice and translational research and clinical applications of approved and experimental radiopharmaceuticals for diagnostic and therapeutic purposes. Papers dealing with advanced preclinical evidence in the fields of physics, dosimetry, radiation biology and radiopharmacy with relevance to upcoming applications in human subjects are also within the scope of the journal. The journal offers in-depth information to nuclear medicine practitioners and allied professionals involved in molecular imaging and therapy. Expert peer-reviewers and a distinguished Editorial Board, which includes internationally renowned experts, make Clinical and Translational Imaging a valuable, authoritative and selective reference tool.
Keywords: Radiology; Interventional radiology; Nuclear medicine; Radiotherapy; Nuclear Medicine; Imaging / Radiology; Diagnostic Radiology; Medical and Radiation Physics; Interventional Radiology; Radiotherapy